"Pengaruh Audit Kinerja Sektor Publik Terhadap Akuntabilitas Publik Dengan Pengawasan Fungsional Sebagai Variabel Moderating " (Studi Empiris pada SKPD Pemerintah Kota Malang) - Sunarti Mahmud; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
; "> ABSTRACTIn this era, along with the demands of society in order to Public Sector Organizations ismaintaining quality, professionalizm, public accountability and value for money in carrying out itsactivities as well as to ensure public accountability by public sector organism. Then required audittoward public sector organization. The purpose of this research is to know “How the influence ofPublic Sector Performance Audit toward Public Accountability, how the influence of FunctionalSupervisior toward Public Sector Performance Audit influencing Public Accountability, and how theinfluence of Functional Supervisior toward the relationship between Public Sector Performance Auditand Public Accountability on SKPD in the Government of Malang City”.The population in theresearch is all of SKPD in the Government of Malang City. The samples that used were Head Office ofSKPD in Malang City by purposive sampling method. Types of data used are primary data. The dataanalysis was used by multiple linier regression analysis. The result of this research shows that PublicSector Performance Audit, Functional Supervisior partially and Functional Supervisior and PublicSector Performance Audit have influence toward Public Accountability. And the Public SectorPerformance Audit and Functional Supervisior simultaneosly have influence toward AccountabilityPublic.Keyword : Public Sector Performance Audit, Accountability Public, Functional Supervisior